IMPLEMENTATION OF BIOFEEDBACK IN A CLOSED LOOP OF HEART RATE VARIABILITY AND PACED BREATHING IN PATIENTS WITH ARTERIAL HYPERTENSION - Kulik, O. L.; Schmidt, O. J.; Belal, S. A. S.; Rank, I. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The effectiveness of biofeedback in a closed loop of heart rate variability (HRV) and paced breathing in patients with arterial hypertension was studied. 61 subjects with arterial hypertension (31 females and 30 males, mean age 56.8 ± 6.2 years) were examined. In accordance with the objective of the study all subjects were divided into 2 groups: 1 – biofeedback group (34 subjects) and 2 – the comparison group (27 subjects). 5 biofeedback sessions were performed in biofeedback group. In the comparison group only two biofeedback sessions were performed – at admission and before discharge from the hospital. Efficacy of biofeedback was evaluated by comparing the values of systolic and diastolic blood pressure (SBP and DBP, respectively), heart rate (HR), HRV indices, indicators of optimality (O), sensitivity (S) and efficiency (E) and BQI index at admission and discharge in both groups of patients. The use of biofeedback in arterial hypertension subjects allowed to achieve better control of heart rate, systolic and diastolic blood pressure and improves HRV indices. The positive dynamics of optimality and the integral BQI values indicated a training effect of regulation systems.